ANALISA PEMIDANAAN TERHADAP PELAKU PENYALAHGUNA NARKOTIKA GOLONGAN I: Analysis Of Punishment Against Perpetrators Of Category I Narcotics Abuse - Ismet Samuel Tahoran; Ermania Widjajanti (Reformasi Hukum Trisakti, 2024)
Narcotics offences are a social phenomenon and a wide range of community life issues exist in the surrounding area. This criminal act will always find its development in terms of quantity and quality by following the changing times. The subject matter of the problem is how the punishment of Class I Narcotics Abusers and Judges' Consideration of Narcotics Offenders. This research is a normative research based on Data analysis is carried out qualitatively and conclusions are drawn using deductive logic, based on the result and conclusiont analysis that has been carried out Criminalisation of Criminal Abusers of Class I Narcotics that the defendant's actions fulfil the elements of Article 127 Paragraph (1) of Law Number 35 of 2009, In imposing punishment on perpetrators of Narcotics or Drug Abusers for themselves, the judge must pay attention to SEMA Number 4 of 2010 in imposing sanctions on the actions of Mhd Hatta Sinaga Als ega, Rehabilitation as an alternative to imprisonment for perpetrators who are victims of narcotics abuse aims to restore health and reduce the risk of recurrence of harmful behaviour. Rehabilitation emphasises physical and mental recovery, as well as social sanctioning of the offender into the community and not imprisonment.